The Future of Built Heritage Conservation (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This collection of theoretical and practical articles explores how critical understandings of heritage, contemporary conservation theory, and adaptive reuse are all contributing towards the idea of heritage as an immaterial, people-focused activity that has the power to include or exclude. This Special Issue offers work that critically evaluates, through experimental and theoretical results, how architectural heritage and adaptive reuse relate to this conception of heritage.